Seismic Evaluation and Design of Petrochemical and Other Industrial Facilities. - Facilities, Task Committee on Seismic Evaluation and Design of Petrochemical (American Society of Civil Engineers, 2020)
This report provides practical recommendations affecting the safety of new and existing petrochemical and other industrial facilities during and following an earthquake.